Effects of Cyproconazole on Copper Corrosion as Environmentally Friendly Corrosion Inhibitor in Nitric Acid Solution - Wang, Shouxu; Tao, Zhihua; He, Wei; Xiao, Dingjuna; Tan, Ze (Asian Journal of Chemistry, 2015)
The inhibiting influence of cyproconazole on the corrosion of copper in 0.5 M HNO3 solution was investigated by means of potentiodynamic polarization and electrochemical impedance spectroscopy. The selective desorption of cyproconazole from copper metal surface was also studied by the differential polarization curves. Phenomenon of chemisorption accompanied by physisorption was proposed from the values of thermodynamics parameters (DG0ads) obtained. Results obtained from the experimental data show that cyproconazole acts as an effective eco-friendly corrosion inhibitor for copper in nitric acid. The adsorption of cyproconazole on copper surface from 0.5 M HNO3 obeys the Langmuir adsorption isotherm.